Light from infinity - The origin of pleroma according to the woek of Ocarot Chaim (Treasures of life) by R. Chaim Vital - intoduction, translation, commentary - Sikora, Tomasz (Filozofia Chrześcijańska, 2021)
The presented text contains an introduction, translation and commentary on the stages of the manifestation of the deity and the pleromatic emanation presented in the Ocarot chajim (Treasures of Life) treatise by rabbi Chajim Vital, a disciple of Isaac Luria. This work is the most systematic display of Lurianic metaphysics. In the introduction, the author situates the position of the treaty in the broader context of Lurianic literature. Then he discusses the diff erences and similarities between the ancient Hebrew concept of prophetic spirit transmission, and the Gnostic, Platonic and Neoplatonic understanding of the process of emanation. The translated source text and commentary analyze the act of self-contraction of infi nity and the emergence of a plerome as given in the form of a dialectical game of linear and circular sefi rots until the final emergence of megaanthropos – Adam Qadmon.